1990
DOI: 10.1002/eji.1830200310
|View full text |Cite
|
Sign up to set email alerts
|

Preferential usage of Vα4 and Vβ10 T cell receptor genes by lymphocytic choriomeningitis virus glycoprotein‐specific H‐2Db‐restricted cytotoxic T cells

Abstract: Correlations between the T cell receptor (TcR) V gene usage and the specificity of T cells have been primarily described for major histocompatibility complex (MHC) class II-restricted helper T cell responses. In the present study the TcR genes expressed by MHC class I-restricted murine cytotoxic T cells (CTL) specific for a major epitope of the lymphocytic choriomeningitis virus (LCMV), LCMV-GP2(275-289), were investigated. The TcR primary structure of an LCMV-GP2(275-289) specific H-2Db-restricted CTL clone h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…It has been reported that T cell lines specific for GP276 were using the V ␤ 10 variable segment for their TCR (26). Naive MECL-1 mice showed no difference in V ␤ 10 usage compared with C57BL/6 (Fig.…”
Section: The Generation Of V ␤ 10b-specific Ctls Is Impaired In Lcmv-mentioning
confidence: 90%
“…It has been reported that T cell lines specific for GP276 were using the V ␤ 10 variable segment for their TCR (26). Naive MECL-1 mice showed no difference in V ␤ 10 usage compared with C57BL/6 (Fig.…”
Section: The Generation Of V ␤ 10b-specific Ctls Is Impaired In Lcmv-mentioning
confidence: 90%
“…The presence of public clonotypes and the global restriction of repertoire cannot be only attributed to the successive and repetitive stimulations of immune cells upon chronic infection, as the above public clonotype appeared early during acute infection (41,42). Different studies have also suggested that the structural constraints/mechanisms of the TCR-pMHC interaction (12,13,43,44) and the endogenous selection of T cells (45) might play an important role in the regulation of the level of TCR diversity.…”
Section: Discussionmentioning
confidence: 99%
“…A factor that was shown to be a determinant of immunodominance at least in influenza infection is the availability of specific CTLs in the repertoire of peripheral T cell specificities (3,25). T cell lines specific for gp276 were strongly biased for the usage of V␣4 and V␤10 variable segements for their TCRs (38), but it has not been investigated whether this bias imposes a limit on the availability of gp276-specific T cells in the repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that T cell lines specific for gp276 were using exclusively the V␤10 variable segment for their TCRs (38). Naive LMP2…”
Section: The Generation Of V␤10b-specific Ctls Is Impaired In Lcmv-inmentioning
confidence: 99%